Creative modelling of clothing in the work of designers: Trends and directions - Serbin, O.; Pashkevych, K. (Art and Design, 2025)
Methods and techniques of creative modelling assisted in creating new proportions, volumetric forms, and silhouettes of clothing during the development of new designer clothing collections. The aim was to examine the application of creative modelling methods in the collections of world designers showcased during Paris Fashion Week. The article was a theoretical study based on a systematic approach and the application of general scientific methods for analysing research objects, such as analytical-typological, artistic-compositional, visual-analytical, and others. Prospective collections of world-renowned Fashion Houses and brands for the spring-summer 2025 season, presented during Paris Fashion Week, were analysed. Collections featuring models that likely employed creative methods, tools, and techniques of modelling were selected. Based on the analysis of models from the chosen collections, probable techniques and means of creative modelling embedded in the garment construction were identified and described. It was established that the most commonly used techniques and means of creative modelling in designers' collections included the integration of geometric shapes into the structure of the garment and its parts, as well as the transformation of sleeves and other details, where parts of the garment were combined into one large, unified piece that smoothly transitioned from one section of the garment to another, enveloping various parts of the human body and creating a visually complex structure. In addition to these techniques, designers also utilised other means of creative modelling, such as remodelling of the base, artistic-decorative division, and others. Models from the collections of world Fashion Houses and brands were described. The research results could be used in the creative activities of clothing designers, in improving the process of clothing design and its form creation, as well as in the educational process for training clothing designers and fashion constructors.